PENGEMBANGAN MEDIA KALENDER PENGINGAT PADA PASIEN TBC DALAM PENCEGAHAN TB-RO (Jurnal Kesehatan Siliwangi, 2023)
Tuberculosis is a direct infectious disease caused by TB bacteria(Mycobacterium Tuberculosis). Discontinuation of treatment in pulmonary TB patientswill cause TB-RO cases. The development of calendar media is carried out as an effortto promote health to prevent an increase in TB-RO cases. Objective: to produce anappropriate calendar media as a reminder to TB patients in TB-RO prevention in theworking area of the Kotakaler Health Center, Sumedang Regency. Methods: Thisresearch is a development research using the ADDIE design model which consists offive stages, namely analysis, design, development, implementation or delivery, andevaluation. The sample in this study were 18 TB patients in the working area of theKotakaler Health Center which were selected using a purposive sampling technique.Results: This study shows that the results of the feasibility test from material expertsare 77.89% and media experts are 71.11%, which means that the media is"appropriate" to be used. Meanwhile, the results of the feasibility test in the small groupwere 93%, which means that the media was "very feasible" to be used. Conclusion:So it can be concluded that the media calendar "Know and Prevent TB-RO" is feasibleto use and can be used as an alternative media for health promotion to prevent TB-RO.Recommendation: this calendar media that has been made can be used as analternative media for health promoters to educate about TB-RO and this research canbe continued to see the effectiveness of this calendar media in increasing knowledgeabout TB-RO.